Synthesis of α-Ketothioamides via Willgerodt–Kindler Reaction of Arylglyoxals with Amines and Sulfur under Solvent-Free Conditions - Eftekhari-Sis, Bagher; Khajeh, Saleh Vahdati; Büyükgüngör, Orhan (Synlett, 2013)
Willgerodt–Kindler reaction of arylglyoxal hydrates with secondary amines and elemental sulfur under solvent-free conditions at 80 °C is developed, in which α-ketothioamides are obtained in 70–90% yield in 0.6–1 hour. The X-ray crystal-structure analysis for one compound was obtained.
Keywords: α-ketothioamides; Willgerodt–Kindler reaction; arylglyoxals; green chemistry; solvent-free